Accommodating the Rise of China and Facing China as a Threat in International Society in the Decade - Nuke Faridha Wardhani (JURNAL HUBUNGAN INTERNASIONAL INDONESIA, 2023)
This paper explains how the international society, mainly the United States and western countries accommodate the rise of China in recent decade. China has enhanced and maintained its capability to be a great power and it is unavoidable phenomenon. Furthermore, after the Cold War ended until this era, it is believed that the international system has changed into multipolar with the presence of China as a potential great power. However, it resulted the fear from other countries about China’s rise and is assumed as a threat for hegemony powers. Eventually, if China’s position in international society in recent time as a threat, then how to deal with it? The other countries can choose between treating China as a partner or a great competitor where China today has built massive capabilities and planned to elevate its strength by using advanced technology. Keywords: the Rise of China, China Threat, International Society, Strategic Partner.